Characteristics and Depositional Processes of Coastal and Marine Sediments of The Northern Part of Obi Island, Molucca. Issue 1 (May 2021) - Zuraida, R; Adhirana, I; Lattuputty, G; Hernawan, U; Gustiantini, L; Hasanah, I; Alam, M; Prasetyo, F B
Abstract: This paper presents the characteristics of coastal and marine sediments of the northern part of Obi Island, Molucca. Grain size analyses were conducted on 24 coastal sediment and 32 marine sediment samples. Taphonomy of Homotrema rubrum was studied on three samples from coral reef that grows on the slope off Laiwui to determine current direction. The mean grain size ranges between 0.01 – 2.6 mm, very well sorted to very poorly sorted, and while skewness varies from very finely skewed to very coarsely skewed. While lithic fragments predominate coastal sediments, biogenic fragments form the majority of marine sediment grains. Textural parameters and sediment composition show three distinctive groups that represent: 1) Akeleletango in the west that is characterized by moderately sorted coarse to fine sand; 2) Tabuji – Laiwui that is characterized by poor to moderately sorted fine granules to fine sand that is interpreted as debris flow deposit; and 3) Anggai in the east that is characterized by poorly sorted coarse sand. Linear discriminate function analysis shows the dominance of shallow marine deposits in beach sediments with strong fluvial influence. The taphonomy of H. rubrum indicates that the prevailing current direction off Obi is westward, which is supported by current observation.